A Review Of Children's Restorative Justice In Minors Criminal Cases - Nurhimmi Falahiyati; Detania Sukarja (Jurnal Scientia, 2024)
The settlement of juvenile cases through restorative justice approach includes: the stages of investigation, prosecution, court and implementation of punishment or action and after serving the punishment or action. The problems in this study are about what factors are used against children in restorative justice in resolving child criminal cases. How is the responsibility of investigators in the implementation of restorative Justice in the settlement of juvenile criminal cases in the PPA Unit of the Langkat Police Criminal Investigation Unit. How are the obstacles and efforts of investigators in the PPA Unit of the Langkat Police Reskrim Unit in the implementation of restorative Justice in the settlement of criminal cases committed by children. Where this research uses an empirical juridical approach method, which tries to describe the application of restorative justice in the settlement of sexual abuse of children committed by minors by the PPA Unit of Satreskrim Polres Langkat. The data source of this research consists of primary and secondary data. The data analysis used is qualitative data analysis. The responsibility of PPA Satreskrim investigators of Langkat Police in implementing restorative Justice in resolving cases of children in conflict with the law is inseparable from the implementation of the duties and functions of investigators specified in the Law on the Child Criminal Justice System, where the implementation of diversion in resolving cases of children in conflict with the law is mandatory (imperative). The obstacle of investigators in the PPA Unit of the Langkat Police Criminal Investigation Unit in the implementation of restorative Justice is the difficulty of bringing together the balance of the various interests of the parties, namely the perpetrator, victim, and society.